IMPLICATIONS OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT KA GUBENG DAOP SURABAYA STATIONS - Setyadarma, Bambang; Poernomo, Tri Tjahjo (Journal of Industrial Engineering & Management Research, 2023)
This research article aims to identify the relevance of the dimensionality implication of service quality (reliability, responsiveness, assurance, empathy, evidence) to consumer satisfaction. The overall dimensionality quality of service has a positive influence relevance to the achievement of consumer satisfaction values meaningfully. Where the statistical histogram curve is suspended towards the formation of an asymmetric curve line between the absis ordinate against the frequency absis. It has a tendency to distribute normally, where the entire particle of a normal patterned observation object is not randomized. Sampling of train service users as many as 60 participants were able to represent the entire population of train service users at gubeng station operational area of surabaya today